Heroic Deeds and Heroic Failure - Carol Sweetenham (Medievalista)
The First Crusade was evoked by Anglo-Norman English historians throughout the 12th and into the 13th Century. In the first third of the 12th Century it was recounted in detail by three leading historians: Orderic Vitalis, William of Malmesbury and Henry of Huntington. By the middle of the 12th Century, however, it was already being depicted less as an enterprise in its own right and more as a backdrop for the participation of Robert, Duke of Normandy. Robert himself was depicted as a flawed hero, whose bravery on crusade was celebrated, but who failed in his ultimate duty by refusing the crown of Jerusalem. This paper traces the evolution of the portrayal both of the crusade and of Robert’s part in it in 12th and 13th Century England, exploring how perceptions both of the crusade and Robert changed in line with political priorities and attitudes to crusade.